Revealing a high water abundance in the upper mesosphere of Mars with ACS onboard TGO - Belyaev, DA; Fedorova, AA; Trokhimovskiy, A; Alday, J; Montmessin, F; Korablev, OI; Lefevre, F; Patrakeev, AS; Olsen, KS; Shakun, AV (Wiley, 2021)
We present the first water vapor profiles encompassing the upper mesosphere of Mars, 100–120 km, far exceeding the maximum altitudes where remote sensing has been able to observe water to date. Our results are based on solar occultation measurements by Atmospheric Chemistry Suite (ACS) onboard the ExoMars Trace Gas Orbiter (TGO). The observed wavelength range around 2.7 μm possesses strong CO2 and H2O absorption lines allowing sensitive temperature and density retrievals. We report a maximum H2O mixing ratio varying from 10 to 50 ppmv at 100–120 km during the global dust storm (GDS) of Martian Year (MY) 34 and around southern summer solstice of MY 34 and 35. During other seasons water remains persistently below ∼2 ppmv. We claim that contributions of the MY34 GDS and perihelion periods into the projected hydrogen escape from Mars are nearly equivalent.